2013
DOI: 10.1590/0074-0276108062013022
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial susceptibility, biofilm formation and genotypic profiles of Staphylococcus haemolyticus from bloodstream infections

Abstract: We analysed the antimicrobial susceptibility, biofilm formation and genotypic profiles of 27 isolates of Staphylococcus haemolyticus obtained from the blood of 19 patients admitted to a hospital in Rio de Janeiro, Brazil. Our analysis revealed a clinical significance of 36.8% and a multi-resistance rate of 92.6% among these isolates. All but one isolate carried the mecA gene. The staphylococcal cassette chromosome mec type I was the most prevalent mec element detected (67%). Nevertheless, the isolates showed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
3
28
0
2
Order By: Relevance
“…In a study of S. haemolyticus isolated from bloodstream infections, 66% of the isolates formed robust biofilms in vitro , but the same strains were all negative for PCR of the ica operon for PIA synthesis (337). This suggests that S. haemolyticus has other means of biofilm formation.…”
Section: Other Staphylococcal Speciesmentioning
confidence: 99%
“…In a study of S. haemolyticus isolated from bloodstream infections, 66% of the isolates formed robust biofilms in vitro , but the same strains were all negative for PCR of the ica operon for PIA synthesis (337). This suggests that S. haemolyticus has other means of biofilm formation.…”
Section: Other Staphylococcal Speciesmentioning
confidence: 99%
“…In contrast to the abundance of information available for S. epidermidis, little is known about biofilm formation of S. haemolyticus, despite the importance of this species in nosocomial infections (Barros et al, 2015). These infections are mostly associated with immune-compromised patients and patients with implanted medical devices (Silva et al, 2013). Most S. haemolyticus strains seem to lack the important virulence attributes.…”
Section: Introductionmentioning
confidence: 99%
“…However, some enzymes, cytolysins or surface substances are indicated in the literature as factors contributing to its virulence (Daniel et al, 2014;Flahaut et al, 2008;Simango, 2005), but none of them was identified as a crucial and determinative factor (Fredheim et al, 2009). Despite this, S. haemolyticus is, after S. epidermidis, the second most frequently isolated CNS from clinical cases, particularly from blood infections, including sepsis (Becker et al, 2014;Klingenberg et al, 2007;Liakopoulos et al, 2008;Silva et al, 2013). Therefore, what is the reason for the increasing clinical significance of S. haemolyticus?…”
Section: Introductionmentioning
confidence: 99%
“…18 S. epidermidis emerged as a common cause of hospital-acquired infections and S. haemolyticus has been identified as an important cause of primary bloodstream infections associated with the use of central venous catheters. 6,21 Furthermore, they have become multiple drug resistant especially to b-lactams. 14 The increasing antibiotic resistance of nosocomial isolates exacerbates this problem and poses a great challenge for the management of hospital-acquired infections in general.…”
Section: Introductionmentioning
confidence: 99%